ESRA19-0271 Intrathecal administration of hyperbaric prilocaine is a source of systemic O-toluidine. (30th August 2019) - Carini, A; Weiss, T; Koslitz, S; Brüning, T; Guntz, E
Abstract : Background and aims: Hyperbaric 2% prilocaine (HP) is increasingly used for spinal anesthesia. It is the only local anesthetic metabolized to o-toluidine, a human bladder carcinogen. Massive increase of o-toluidine hemoglobin adducts (HAoT), a marker of o-toluidine carcinogenic pathway, was described following subcutaneous injection. In the present study we aimed to assess a single intrathecal dose of HP as a source of HAoT and urinary o-toluidine (UoT). Methods: After ethical committee approval and informed written consent, 10 patients undergoing surgery received 50 mg of HP intrathecally. Blood and urine samples were collected before injection and up to 24 hours later. UoT and HAoT were measured by tandem mass-spectrometry after gas-chromatographic separation. Values are expressed as mean ± standard deviation. Pair Students t-test was used for the significance tests. Results: Intrathecal administration of 50 mg of HP leads to a massive increase of HAoT (0.11±0.02 to 11.59±1.89 ng/g Hb after 24h, p<0.0001, figure 1 ). Peak of UoT was observed after 8h (0.1±0.1 to 351.6±352.7 µg/L, p<0.001) and declined to 80.0±66.8 µg/L after 24h (figure 2 ). Conclusions: Intrathecal administration of HP leads to a relevant systemic burden of carcinogenic o-toluidine. Therefore, the carcinogenic risk of HP administration should be the object of ethical considerations and further clinical investigations.